Characteristics of Patients with HIV/AIDS Undergoing Antiretroviral Therapy at Loa Bakung Community Health Center - Relung Adiniah Permani; Irfansyah Baharuddin Pakki; Akmad Azmiardi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : HIV is a virus that attacks the body’s immune system, making the body more susceptible to various infections. AIDS refers to a collection of symptoms and infections associated with a weakened immune system due to HIV infection. Loa Bakung Community Health Center is one of the healthcare facilities in Samarinda that provides ART services for patients with HIV/AIDS. Objective : This study aims to describe characteristics of patients with HIV/AIDS undergoing ART at Loa Bakung Community Health Center. Research Methods/ Implementation Methods : This study used a retrospective descriptive method with secondary data from medical records and SIHA 2.1 application. The population included all HIV/AIDS patients undergoing ART at Loa Bakung Community Health Center from January 2023 to December 2024. The data were analyzed descriptively and presented in the form of frequency distribution tables and percentages. Results : Of the 33 HIV/AIDS patients undergoing ART, the majority were male (64%) aged 20-39 years (84%) and had a high school education (76%). Most patients were employed (55%) and single (52%). The largest population group was partners of key populations/PLHIV/STI patients (42%), followed by men who have sex with men (MSM) at 37%. The dominant ART regimen used was TLD (Tenofovir, Lamivudine, Dolutegravir) at 58%, with 87% of patients tested showing suppressed viral load results. Conclusion/Lesson Learned : Increasing early detection, education on risky sexual behaviors, and optimizing counseling and patient support services are strategic steps to improve the success of ART and reduce the rate of HIV transmission.